First principles and integrated modelling achievements towards trustful fusion power predictions for JET and ITER. (5th July 2019) - Garcia, J.; Dumont, R.J.; Joly, J.; Morales, J.; Garzotti, L.; Bache, T.W.; Baranov, Y.; Casson, F.J.; Challis, C.; Kirov, K.; Mailloux, J.; Saarelma, S.; et al.
Abstract: Predictability of burning plasmas is a key issue for designing and building credible future fusion devices. In this context, an important effort of physics understanding and guidance is being carried out in parallel to JET experimental campaigns in H and D by performing analyses and modelling towards an improvement of the understanding of DT physics for the optimization of the JET-DT neutron yield and fusion born alpha particle physics. Extrapolations to JET-DT from recent experiments using the maximum power available have been performed including some of the most sophisticated codes and a broad selection of models. There is a general agreement that 11–15 MW of fusion power can be expected in DT for the hybrid and baseline scenarios. On the other hand, in high beta, torque and fast ion fraction conditions, isotope effects could be favourable leading to higher fusion yield. It is shown that alpha particles related physics, such as TAE destabilization or fusion power electron heating, could be studied in ITER relevant JET-DT plasmas.